Implementation of a virtual, shared medical appointment program that focuses on food as medicine principles in a population with obesity: the SLIM program - Kirbach, Kyleigh; Marshall-Moreno, Imani; Shen, Alice; Cullen, Curtis; Sanigepalli, Shravya; Bobadilla, Alejandra; MacElhern, Lauray; Grunvald, Eduardo; Kallenberg, Gene; Tristão Parra, Maíra; Sannidhi, Deepa (Frontiers in Nutrition, 2024)
Background: Multimodal lifestyle interventions, employing food as medicine, stand as the recommended first-line treatment for obesity. The Shared Medical Appointment (SMA) model, where a physician conducts educational sessions with a group of patients sharing a common diagnosis, offers an avenue for delivery of comprehensive obesity care within clinical settings. SMAs, however, are not without implementation challenges. We aim to detail our experience with three implementation models in launching a virtual integrative health SMA for weight management. Methods: Eligible patients included individuals 18 years of age or older, having a body mass index (BMI) of 30 kg/m 2 or 27 kg/m 2 or greater with at least one weight related comorbidity. The Practical, Robust Implementation and Sustainability Model (PRISM), Plan, Do, Study, Act (PDSA), and the Framework for Reporting Adaptations and Modifications-Enhanced (FRAME) models were applied to guide the implementation of the Supervised Lifestyle Integrative Medicine (SLIM) program, a virtually delivered, lifestyle medicine focused SMA program, in a weight management clinic within a major health system. We describe how these models, along with attendance for the initial cohorts, were used for decision-making in the process of optimizing the program. Results: 172 patients completed the SLIM program over two years.